Using a diagnostic model based on routine laboratory tests to distinguish patients infected with SARS-CoV-2 from those infected with influenza virus. (June 2020) - Luo, Ying; Yuan, Xu; Xue, Ying; Mao, Liyan; Lin, Qun; Tang, Guoxing; Song, Huijuan; Liu, Weiyong; Hou, Hongyan; Wang, Feng; Sun, Ziyong
Highlights: Novel coronavirus pneumonia patients are frequently encountered in the sixth and seventh decades of life Significantly decreased white blood cells, alkaline phosphatase and d-dimer were observed in novel coronavirus pneumonia patients compared with influenza patients Lactate dehydrogenase, erythrocyte sedimentation rate and fibrinogen were significantly increased in novel coronavirus pneumonia patients compared with those in influenza patients An optimal diagnostic model with moderate value was established based on the combination of 18 biomarkers from routine laboratory tests to discriminate novel coronavirus pneumonia patients from influenza patients Abstract: Background: The differential diagnosis between novel coronavirus pneumonia patients (NCPP) and influenza patients (IP) remains a challenge in clinical practice. Methods: Between January 2018 and March 2020, 1, 027 NCPP and 1, 140 IP were recruited from Tongji hospital. Routine blood examination, biochemical indicators and coagulation function analysis were simultaneously performed in all participants. Results: There was no sex predominance in NCPP. The NCPP were frequently encountered in the sixth and seventh decades of life. The mean age of NCPP (56 ± 16 years) was higher than IP (47 ± 17 years), but without statistical difference. Although most results of routine laboratory tests between NCPP and IP had no significant differences, some laboratory tests showed an obvious change in NCPP. It was observed that NCPP had significantly decreased white blood cells, alkaline phosphatase and d-dimer compared with IP. However, the results of lactate dehydrogenase, erythrocyte sedimentation rate and fibrinogen were significantly increased in NCPP compared with IP. The diagnostic model based on a combination of 18 routine laboratory indicators showed an area under the curve of 0.796 (95% CI, 0.777–0.814), with a sensitivity of 46.93% and specificity of 90.09% when using a cut-off value of 0.598. Conclusions: Some routine laboratory results had statistical difference between NCPP and IP. A diagnostic model based on a combination of routine laboratory results provided an adjunct approach in the differential diagnosis between NCPP and IP.